Molecular characterization and phylogenetic analysis of Trypanosoma spp. detected from striped leaf-nosed bats (Hipposideros vittatus) in Zambia. (August 2019) - Qiu, Yongjin; Kajihara, Masahiro; Harima, Hayato; Hang'ombe, Bernard Mudenda; Nakao, Ryo; Hayashida, Kyoko; Mori-Kajihara, Akina; Changula, Katendi; Eto, Yoshiki; Ndebe, Joseph; Yoshida, Reiko; Takadate, Yoshihiro; et al.
Abstract: Bat trypanosomes consist of more than 30 trypanosome species from over 70 species of bats. Recent studies suggest that bats play a role in disseminating trypanosomes from African continent to the terrestrial mammals both in the Afrotropic-Palearctic Ecozones and Nearctic Ecozone. However, the diversity, distribution, and evolution of bat trypanosomes are still unclear. To better understand their evolution, more genetic data of bat trypanosomes from a variety of locations are required. During a survey of Borrelia spp. of bats inhabiting a cave in Zambia, we observed flagellate parasites from 5 of 43 hemocultures. Sequence and phylogenetic analyses of the glycosomal glyceraldehyde 3-phosphate dehydrogenase gene ( gGAPDH ; 572 bp) and the 18S ribosomal RNA gene (18S rRNA gene; 1, 079–1, 091 bp) revealed that all were Trypanosoma spp. belonged to the Trypanosoma cruzi clade. Three and two of them exhibited the similarity with T. conorhini and T. dionisii, respectively. The present study provides the first genetic data on Trypanosoma spp. of bats inhabiting Zambia. Graphical abstract: Image 1 Highlights: Two putative species of trypanosomes were detected from bats. First molecular characterization of bat trypanosome in Zambia. First record of trypanosome in Hipposideros vittatus .